2009
DOI: 10.3945/jn.109.108845
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Milk, but Not Formula, Regulates the Immune Response to β-Lactoglobulin in Allergy-Prone Rat Pups

Abstract: Controversy exists regarding the timing of the introduction of allergic foods into the diet. We investigated the immune response of rat pups exposed to beta-lactoglobulin (BLG), one of the main allergenic proteins in cow milk. Brown Norway allergy-prone rats were allocated into groups: dam-reared and unchallenged (DR), DR challenged with BLG via gavage (11 mg/d), or rats fed via gastric cannula a formula containing BLG (11 mg/d). BLG was given from d 4 of life. Rats were killed at d 10, 14, or 21. Sera were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Despite a recent report according to which commercially available pasteurized cow's milk may contain significant amounts (up to 1.5 ng/ml) of bovine TGF-␤ 2 which remains immunologically active in vitro and in vivo [22] , it is not known whether bovine TGF-␤ is present in infant formula. In experiments conducted using a rat model, it has been demonstrated that maternal milk protects rat pups from developing detrimental immune responses to orally administered bovine ␤ -lactoglobulin [23] . In line with this, feeding infant formula to rat pups results in an allergic-type immune response which is significantly reduced if the formula is supplemented with breast milk levels of TGF-␤ [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite a recent report according to which commercially available pasteurized cow's milk may contain significant amounts (up to 1.5 ng/ml) of bovine TGF-␤ 2 which remains immunologically active in vitro and in vivo [22] , it is not known whether bovine TGF-␤ is present in infant formula. In experiments conducted using a rat model, it has been demonstrated that maternal milk protects rat pups from developing detrimental immune responses to orally administered bovine ␤ -lactoglobulin [23] . In line with this, feeding infant formula to rat pups results in an allergic-type immune response which is significantly reduced if the formula is supplemented with breast milk levels of TGF-␤ [24] .…”
Section: Discussionmentioning
confidence: 99%
“…FOXP3 TSDR demethylation was significantly lower in children with active IgE-mediated CMA than in either children who outgrew CMA or in healthy children [186]. Maternal rat milk in comparison with miRNA-deficient artificial formula increased mesenteric lymph node FoxP3 expression and decreased serum IgE levels to β-lactoglobulin in allergy-prone rat pups [197]. Thus, milk miRNAs operate like DNMT inhibitors that increase the stability of FOXP3 gene expression enhancing the suppressive capacity of Tregs, promoting an immune tolerance environment [198].…”
Section: Activation Of Developmental Genes Via Dna Cpg Demethylationmentioning
confidence: 99%
“…In an animal model, Strobel et al [14] have shown that oral OVA given in the first week of life to mice induces humoral as well as cell-mediated immunity [14]. In contrast, recent studies associate early antigen exposure with development of tolerance [15, 16]. More research is required to determine the optimum intervention strategy to promote oral tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between breastfeeding and allergy prevention is controversial [2426], there has recently been a growing interest in the role of breast milk in regulating immune response development to food antigens as new foods are introduced into the diet [16, 27]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation